A Comparison of Point-of-Care Instruments Designed for Monitoring Oral Anticoagulation with Standard Laboratory Methods - Gosselin, Robert; Owings, John T.; White, Richard H.; Hutchinson, Rose; Branch, Jennifer; Mahackian, Kathy; Johnston, Marilyn; Larkin, Edward C. (Thrombosis and Haemostasis, 2000)
Our study compared point-of-care (POC) device monitoring with traditional clinical laboratory methods device of patients on oral anticoagulant therapy. The POC devices used in the study were Coumatrak, CoaguChek, CoaguChek Plus, Thrombolytic Assessment System (TAS) PT-One, TAS PTNC, TAS PT, Hemachron Jr. Signature, Protime Microcoagulation System, and Medtronics ACT II. The clinical laboratory method used thromboplastins with different ISI values: Innovin and Thromboplastin C Plus (TPC). All POC INRs showed strong correlation with both laboratory methods, with correlation coefficients of >0.900. All POC methods demonstrated a significant (p <0.05) difference in INR values, except the TAS PTNC and ACT II INRs (p: 0.12 and 0.71 respectively) when compared with Innovin INRs. All POC INRs were significantly different from TPC generated INRs (p <0.05). Comparisons of the POC INRs to the group mean of the POC methods, show higher correlation (R>0.93), but there were still significant (p<0.05) differences noted between the POC group INR mean and CoaguChek Plus, ACT II, TAS PT-One, TAS PTNC, and Hemachron Jr Signature INRs. These data indicate that POC INR biases exist between laboratory methods and POC devices. Until a suitable whole blood INR standardization method is available, we conclude that clinicians using point-of-care anticoagulation monitoring should be aware of differences between POC and parent laboratory values.
Keywords: International Normalized Ratio (INR); point-of-care devices; coumadin monitoring